A reivindicação do estatuto jornalístico nas histórias em quadrinhos de Joe Sacco - Flavio Pinto Valle (2010)
This dissertation presents an attempt to approach comics journalism, a medium located in the intersection between journalism and comics. Because comic journalism is a communicative practice in a bordering area, where constraints and opportunities present themselves with greater force, an approach is necessary to understand the displacements that it operates in relation to the more standardized practices found ontheir original media. However, before dealing with specific issues of journalism in comics, this study intends to recover the relationships that the comic has been keeping to journalism since the mid-nineteenth century, when the first sequential graphic narrative was published in newspapers. After this historical approach, it proposes a reflection on the comics reportages by Joe Sacco, more specifically, about his claim to the journalistic status of his comics. Unlike other journalists of comics, Sacco doesnt stand solely in one narrative position: he is the character, the narrator and the author of his narratives. Thus, he turns his reportages into autobiographic documents that found on the self who writes the criterion that must be evaluated. The reporter constructs him self through its inclusion in the journalistic community that is defined by a set of ethical values and technical standards to guide its members in performing their professional activities. In this sense, Sacco supports his claim to the journalistic status on the assertion of professional identity at each narrative position of his comics reportages. However, by appropriating the ethical values and technical standards of journalism, the reporter, in addition to legitimize his claim, weaves a critique of bureaucratic exercise of journalism, and proposes the rescue of a romantic vision of the profession.